Exploring Euphemisms in Bridgerton: Diamond of the First Water - Alvia Nurrahma Ekasiwi; Barli Bram (Institut Agama Islam Negeri Palopo, 2022)
The development of language affects speech cultures and modes of communication. Politer terms were created to avoid misunderstanding. This phenomenon is called euphemism. Employing euphemisms while discussing sensitive topics can help people express their ideas politely. This present study aims to determine the types of euphemism used in a famous television series entitled Bridgerton. The research was conducted only on the first episode of the series. This qualitative research employed content analysis as the research methodology. The research findings showed six types of euphemism identified, namely substitution, litotes, metonym, hyperbole, synecdoche, and colour-based metaphor for x-phemism. Nevertheless, this research was only analyzing the first episode of the series. Hence, the results might have differed in other episodes. Future researchers who are interested in the same topic may find other types of euphemisms that this research cannot cover.